Immunohistochemical quantification of substance P in spinal dorsal horns of patients with multiple system atrophy. Issue 6 (June 1991) - Tomokane, N; Kitamoto, T; Tateishi, J; Sato, Y
Abstract : Using a computer-assisted image analyser, an immunohistochemical quantification method of substance P-like immunoreactivity (SPLI) in laminae I + II of spinal dorsal horn was established and applied to 13 patients with multiple system atrophy (MSA) with no disturbance of pain sensation, including olivo-ponto-cerebellar atrophy and striatonigral degeneration, and 13 neurologically normal controls. To investigate whether alteration of SPLI is related to an autonomic disorder, myelinated fibre counts of the fourth thoracic ventral roots were performed. Eleven of 13 MSA patients showed a significant decrease in small and large myelinated fibres, and were diagnosed with definite Shy-Drager syndrome (SDS), with the exception of two who had no apparent history of autonomic dysfunction. SPLIs in laminae I + II in 10 of these 11 patients, when adjusted for age, were significantly decreased at both levels of the fourth thoracic and third lumbar spinal segments. The results suggest the disorder of SP-containing synapses of primary afferent neurons and/or those of interneurons in SDS.